The Skills Road : Skills for Employability in the Kyrgyz Republic - Ajwad, Mohamed Ihsan; de Laat, Joost; Hut, Stefan; Larrison, Jennica; Abdulloev, Ilhom; Audy, Robin; Nikoloski, Zlatko; Torracchi, Federico (World Bank, Washington, DC, 2014)
This report is about education, skills, and labor market outcomes in the Kyrgyz Republic. The report shows that skills are valued in the Kyrgyz Republic labor market, yet skills gaps persist. Three findings are particularly noteworthy. First, higher skilled youth have better employment outcomes, meaning that youth with more cognitive and non-cognitive skills are more likely to be employed than inactive or discouraged youth. Second, workers with higher cognitive and non-cognitive skills are more likely to use those skills in their daily work. Third, workers with higher skills—cognitive skills especially—tend to have higher quality (formal sector, less repetitive tasks, less physical work) jobs. However, large variations in observed skills among those with the same level of educational attainment indicate that formal education is failing too many people, even though skill development occurs at different stages in the life cycle and a host of actors are involved—families, for example, play a central role. The report argues that the government could shift some of its focus from providing access to educational institutions and instead focus on providing the skills (cognitive, non-cognitive, and technical) students need to succeed as adults. The government can also do more to get children off to the right start by investing in early childhood development programs, where rates of return to investment are generally very high and important soft skills are learned. Finally, more can be done to match the supply of skills with employer demand by improving the use of information in matching skills to jobs in the labor market.